IMF COVID-19 Response-A New Short-Term Liquidity Line to Enhance The Adequacy Of The Global Financial Safety Net. (Policy Papers; Policy Paper, 2020)
The COVID-19 pandemic has created severe disruption in the global financial system, with many emerging market and developing countries (EMDCs) facing liquidity shortages. In the context of intensified demand for liquidity and heightened global uncertainty, staff has revisited the 2017 proposal for a new facility to provide liquidity support to the Fund's membership. This paper proposes the establishment of a new Short-term Liquidity Line (SLL) as a special facility in the General Resources Account (GRA), based on the key features of the 2017 blueprint.